Choques macroeconômicos e a probabilidade de permanecer empregado ou desempregado - Marco Antônio Freitas de Hollanda Cavalcanti; Ajax Reynaldo Bello Moreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This exercise contributes to the literature that relates macroeconomic cycle with the labor market, estimating an Favar model to Brazil with four variables - degree of utilization, inflation rate, Selic rate and real exchange rate - and a latent variable that summarizes the state of the labor market, which is represented with the odds of being employed, stay employed and remain unemployed in different demographic groups. The shocks - demand, supply, monetary, foreign exchange and social - are identified, using the signal response of a structural macroeconomic model, the Dynamic Stochastic General Equilibrium (DSGE). The results confirm that the labor market is affected by cycle through the fluctuations of contracts.
Keywords: E24; E32; J24; J31; 330; macroeconomic cycle; labor market; heterogeneity